Customer Orientation sebagai penentu Kinerja Usaha yang dimediasi oleh perilaku inovasi dan innovativeness pada UMKM bidang produksi Handicraft di Kota Medan - Nadila Syaztika Dilla; Sarah Imelda; T Lyaza Tahura (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2022)
This study aims to determine customer orientation as a determinant of business performance whichis mediated by innovation behavior and innovativeness in MSMEs in the field of handicraftproduction in Medan City. The research design of moderated multiple linear regression analysis isused as an analytical tool to determine how the influence between the independent and dependentvariables is moderated by the moderating variable. This research uses associative research with aquantitative approach. The population and samples in this study, namely to fill out the google formquestionnaire based on the owners and employees of the Handicraft SMEs, the population based ongender, based on age (20-60 years), based on the length of business establishment (1-20 years) asample of 100 owners Handicraft business in Medan City.The results show that customer orientationhas a significant effect on business performance (t count 3,007 and significance 0.000 <0.05),customer orientation has a positive and significant effect on innovation behavior (t count 5.741 andsignificance 0.000 <0.05), customer orientation has a significant effect on innovativeness (t count5.212 and significance 0.00 < 0.05), innovativeness has a significant effect on business performance(t count 2.256 and significance 0.026 < 0.05), innovation behavior has no significant effect onbusiness performance (t count -1.253 and significance 0.213> 0.05), innovation behavior mediatescustomer orientation towards business performance (t count 0.0014 and significance 0.00 <0.05)innovativeness mediates customer orientation towards business performance (t count 0.015 andsignificance 0.00<0 ,05 )